Ingredients from Litsea garrettii as Potential Preventive Agents against Oxidative Insult and Inflammatory Response. (20th March 2018) - Li, Yan-Ru; Li, Guo-Hui; Sun, Lin; Li, Lin; Liu, Yue; Kong, De-Gang; Wang, Shu-Qi; Ren, Dong-Mei; Wang, Xiao-Ning; Lou, Hong-Xiang; Shen, Tao
Abstract : Oxidative stress and inflammation undoubtedly contribute to the pathogenesis of many human diseases. The nuclear transcription factor erythroid 2-related factor (Nrf2) and the nuclear factor κ B (NF- κ B) play central roles in regulation of oxidative stress and inflammation and thus are targets for developing agents against oxidative stress- and inflammation-related diseases. Our previous study indicated that the EtOH extract of Litsea garrettii protected human bronchial epithelial cells against oxidative insult via the activation of Nrf2. In the present study, a systemic phytochemical investigation of L. garrettii led to the isolation of twenty-one chemical ingredients, which were further evaluated for their inhibitions on oxidative stress and inflammation using NAD(P)H:quinone reductase (QR) assay and nitric oxide (NO) production assay. Of these ingredients, 3-methoxy-5-pentyl-phenol (MPP, 5) was identified as an Nrf2 activator and an NF- κ B inhibitor. Further studies demonstrated the following: (i) MPP upregulated the protein levels of Nrf2, NAD(P)H:quinone oxidoreductase 1 (NQO1), and glutamate-cysteine ligase regulatory subunit (GCLM); enhanced the nuclear translocation and stabilization of Nrf2; and inhibited arsenic [As(III)]-induced oxidative insult in normal human lung epithelial Beas-2B cells. And (ii) MPP suppressed the nuclear translocation of NF- κ B p65 subunit; inhibited the lipopolysaccharide- (LPS-) stimulated increases of NF- κ B p65 subunit, COX-2, iNOS, TNF- α, and IL-1 β ; and blocked the LPS-induced biodegrade of I κ B- α in RAW 264.7 murine macrophages. Taken together, MPP displayed potential preventive effects against inflammation- and oxidative stress-related diseases.